2008
DOI: 10.1021/jp710475g
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Absorption on Na2ZrO3:  A Kinetic Analysis of the Chemisorption and Diffusion Processes

Abstract: The kinetics analysis of carbon dioxide (CO 2 ) chemisorption on sodium zirconate (Na 2 ZrO 3 ), which implies a sodium diffusion process, was investigated. Initially, Na 2 ZrO 3 was analyzed by X-ray diffraction, scanning electron microscopy, and N 2 adsorption, to characterize the material. Finally, the material was thermally analyzed under a CO 2 flux. Later, different isothermal experiments were performed under a CO 2 flux to study kinetically the CO 2 chemisorption on Na 2 ZrO 3 . Results showed that ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
106
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(126 citation statements)
references
References 26 publications
19
106
1
Order By: Relevance
“…[16] Among a variety of materials reported in this category, this section describes in detail adsorption on a representative oxide, calcium oxide, along with a discussion of other important metal-based adsorbents including magnesium oxides and lithium zirconates. Although we focus attention here on calcium oxides and magnesium oxides, it should be noted that many other metal oxides display some CO 2 adsorption properties under selected conditions including lithium oxides, [98] sodium oxides, [99][100][101][102] potassium oxides, [103,104] rubidium oxides, [105] cesium oxides, [106] barium oxides, [107] iron oxides, [108][109][110][111][112] tantalum oxides, [113] copper oxides, [114,115] chromium oxides, [116][117][118][119][120] and aluminum oxides. [121][122][123][124][125][126] where M can be, for example, Mg, Ca, Sr, Ba.…”
Section: Metal-based Adsorbentsmentioning
confidence: 99%
“…[16] Among a variety of materials reported in this category, this section describes in detail adsorption on a representative oxide, calcium oxide, along with a discussion of other important metal-based adsorbents including magnesium oxides and lithium zirconates. Although we focus attention here on calcium oxides and magnesium oxides, it should be noted that many other metal oxides display some CO 2 adsorption properties under selected conditions including lithium oxides, [98] sodium oxides, [99][100][101][102] potassium oxides, [103,104] rubidium oxides, [105] cesium oxides, [106] barium oxides, [107] iron oxides, [108][109][110][111][112] tantalum oxides, [113] copper oxides, [114,115] chromium oxides, [116][117][118][119][120] and aluminum oxides. [121][122][123][124][125][126] where M can be, for example, Mg, Ca, Sr, Ba.…”
Section: Metal-based Adsorbentsmentioning
confidence: 99%
“…For example, alkali zirconates, Li 2 ZrO 3 , and Na 2 ZrO 3 , only can absorb 0.287 g CO2 /g ceramic and 0.237 g CO2 /g ceramic , respectively. 4,5,20 Finally, Li 4 SiO 4 is able to absorb theoretically up to 0.733 g CO2 /g ceramic , assuming that the whole lithium participate in the reaction. Figure 2.…”
mentioning
confidence: 99%
“…Although this kind of thermal trend has not been observed for other lithium ceramics, it has been published that other alkali ceramics presents a similar behavior. 5,20 In those cases, the whole chemisorption process is divided in two steps: First, at low temperatures, a superficial reaction is produced. At this moment, an external alkali carbonate shell is formed over the surface of the ceramic particles.…”
mentioning
confidence: 99%
“…Their results showed that nanocrystalline Na 2 ZrO 3 is a very promising CO 2 acceptor for different applications due to its excellent stability and durability 17 and to be able to work at CO 2 partial pressure as low as 0.025 bar. Based on measuring the isotherms of CO 2 sorption and kinetic analysis, Alcerreca-Corte et al 18 investigated the CO 2 absorption on Na 2 ZrO 3 and found that there are two different processes taking place: (1) CO 2 chemsorption over surface of the particles; (2) once the Na 2 CO 3 shell formed, the second process of Na diffusion from core of the particles to the surface to reactive the first chemsorption process. Obviously, the second step is the limiting step of the total absorption process as the estimated activation energies of these two steps are 33.866 kJ/mol and 48.009 kJ/mol, respectively.…”
mentioning
confidence: 99%